Petting Zoo Animals as an Emerging Reservoir of Extended-Spectrum β-Lactamase and AmpC-Producing Enterobacteriaceae - Shnaiderman-Torban, Anat; Steinman, Amir; Meidan, Gal; Paitan, Yossi; Abu Ahmad, Wiessam; Navon-Venezia, Shiri (Frontiers in Microbiology, 2019)
ESBL and AmpC-producing Enterobacteriaceae (ESBL/AmpC-E) have become a great concern in both human and veterinary medicine. One setting in which this risk could be particularly prominent is petting zoos, in which humans, especially children, directly and indirectly, interact with the animals. Yet, while the zoonotic transmission of various Enterobacteriaceae has been reported previously in petting zoos, reports on ESBL/AmpC-E shedding in this setting is currently lacking, despite the high potential risk. To fill this knowledge gap, we conducted a prospective cross-sectional study to explore the prevalence, molecular epidemiology, and risk for shedding of ESBL/AmpC-E in petting zoos. We performed a prospective cross-sectional study in eight petting zoos. Altogether, we collected 381 fecal and body-surface samples from 228 animals, broth-enriched them, and then plated them onto CHROMagarESBL-plates for ESBL/AmpC-E isolation. Next, we identified the isolated species and tested their susceptibility to various antibiotics using the Vitek-2 system, determined bacterial relatedness by multilocus sequence typing (MLST), and identified ESBL/AmpC genes by using PCR and sequencing. Finally, we asked petting zoo owners and veterinarians to complete questionnaires, which we then analyzed to evaluate risk factors for ESBL/AmpC-E shedding. We found that ESBL/AmpC-E shedding is an important, currently oversighted risk in petting zoos, as the overall shedding rate was 12% (35 isolates, including 29% ESBL-producers, 34% AmpC-producers, and 37% ESBL and AmpC-producers). The isolated bacteria included Enterobacter cloacae (55%), Escherichia coli (31%), and Citrobacter freundii (14%), with diverse ESBL genes. MLST revealed diverse sequence types (STs), including the highly virulent Enterotoxigenic ST656 and the Uropathogenic ST127 Escherichia coli strains, indicating complex epidemiology with inter-animal bacterial transmission. Shedding was associated with petting permission and antibiotic treatment in the petting zoo (OR = 7.34), which were identified as risk factors for ESBL/AmpC shedding. Our findings highlight petting zoos as a source for antibiotics-resistant ESBL/AmpC-producing bacteria, including highly virulent, disease-associated MDR E. coli strains. As this risk has not been previously described in detail, it calls for the implementation of infection control and active surveillance programs in petting zoos and raises the need for a comprehensive guideline to restrain this emerging concern.